Innovativeness Orientation Behaviors and Delinquent Behavioral Change : A Case Study of Ex-Juvenile Entrepreneurial Orientation in Katsina State, Nigeria - - Usman, Bilyaminu; Sharizal, Hashim; Lamptey, Jeff; Ashemi, Baba Ali; Wasilu, Suleiman; Aisha, Yusuf Bilyaminu (Human Resource Management Academic Research Society, 2020)
Modern Entrepreneurship argument discovered the importance and the positive influence of innovativeness orientation behaviors as one of the Entrepreneurial orientations (EO) towards organizational performance and profitability. However, discussion of innovativeness orientation behaviors in the context of individuals such as entrepreneurs behavioral change influence still silent, specifically ex-juvenile entrepreneurs’ context that can give an understanding into the Entrepreneurship framework of knowledge. Therefore, the purposes of the research are to understand the role of innovation orientation as one of the Individual Entrepreneurial Orientations (IEO) towards the delinquent behavioral change of ex-juvenile entrepreneurs. The study employed qualitative methods and in-depth interview to 10 research participants of exjuvenile entrepreneurs that operate entrepreneurial activities in Katsina state, Nigeria. The study used thematic analysis and NVivo 12 Pro to organize and analyze the data. The study found that ex-juvenile entrepreneurs are innovators and more importantly innovation orientation behaviors has a positive influence on ex-juvenile entrepreneurs’ delinquent behavioral change. This finding provides a fresh knowledge about the IEO innovativeness orientation potentiality in the entrepreneurs’ self-development and perception into the entrepreneurship policymakers.